Catastrophic health expenditure of cancer patients at the end-of-life: a retrospective observational study in China - Anli Leng; Jun Jing; Stephen Nicholas; Jian Wang (BMC Palliative Care, 2019)
Abstract Background Cancer is the second leading cause of death globally, causing a substantial economic burden on cancer suffers and their families. The aim of this study is to explore the prevalence, determinants and consequences of catastrophic health expenditure (CHE) among urban and rural end-of-life (EOF) cancer patients in China. Methods Using respondent-driven sampling and face-to-face interviews, field research was conducted with a specialist questionnaire. Data were collected on 792 cancer patients who died between June 2013 and June 2016 in China. The determinants of household catastrophic expenditure were identified by multivariate logistic regression. Findings It is found that more than 80% of cancer patients received life-extending treatment. Extremely high rates of CHE were identified among EOL cancer patients, at 94.3% for urban families and 96.1% for rural families. After spending for health, 84.1% of urban and 91.1% rural EOL cancer patient households were impoverished, falling below the poverty line. For both urban and rural households, income was the most significant factor associated with catastrophic health expenditure (CHE). Health insurance did not adequately compensate for CHE. Rural families experienced higher CHE, lower levels of health care utilization, a different mix of health care access and higher rates of borrowing for out-of-pocket (OOP) health care expenditures than urban families. Both urban and rural households suffered long-term economic disadvantage due to CHE and borrowing for OOP medical care expenses. Conclusions EOL cancer patients experienced severe CHE, with families forced into poverty. With only about 1% of EOL cancer patients receiving palliative care, developing palliative care services and expanding the acceptance of palliative care in China is both urgent and essential. To help address impoverishment due to CHE, China should also develop targeted programs to reduce income inequality, especially rural-urban inequalities; increase access to health care; and accelerate health reform. Increasing the retirement age would provide households with more savings and wealth to withstand CHE.